Can Mobile-Linked Bank Accounts Bolster Savings? Evidence from a Randomized Controlled Trial in Sri Lanka - de Mel, Suresh; McIntosh, Craig; Sheth, Ketki; Woodruff, Christopher (The Review of Economics and Statistics, 2022)
We introduce a new mobile money interface that permits Sri Lankans to deposit mobile airtime balances directly into a formal bank account. Randomizing access and prices, we find a small increase in savings deposits with the partner institution and formal banks more generally, but no change in overall savings. When the deposit transaction costs are completely removed, only 26% use the mobile deposit service and only 7% use it frequently. Our results imply that deposit transaction costs are not a significant barrier to increasing savings, limiting the potential gains of mobile-linked savings products for financial inclusion.